The Gain-of-Function p53 R248W Mutant Promotes Migration by STAT3 Deregulation in Human Pancreatic Cancer Cells - Klemke, Luisa; Fehlau, Clara F.; Winkler, Nadine; Toboll, Felicia; Singh, Shiv K.; Moll, Ute M.; Schulz-Heddergott, Ramona (Frontiers in Oncology, 2021)
Missense p53 mutations (mutp53) occur in approx. 70% of pancreatic ductal adenocarcinomas (PDAC). Typically, mutp53 proteins are aberrantly stabilized by Hsp90/Hsp70/Hsp40 chaperone complexes. Notably, stabilization is a precondition for specific mutp53 alleles to acquire powerful neomorphic oncogenic gain-of-functions (GOFs) that promote tumor progression in solid cancers mainly by increasing invasion and metastasis. In colorectal cancer (CRC) we recently established that the common hotspot mutants mutp53R248Q and mutp53R248W exert GOF activities by constitutively binding to and hyperactivating STAT3. This results in increased proliferation and invasion in an autochthonous CRC mouse model and correlates with poor survival in patients. Comparing a panel of p53 missense mutations in a series of homozygous human PDAC cell lines, we show here that similar to CRC the mutp53R248W protein again undergoes a strong Hsp90-mediated stabilization and selectively promotes migration. Highly stabilized mutp53 is degradable by the Hsp90 inhibitors Onalespib and Ganetespib, and correlates with growth suppression, possibly suggesting therapeutic vulnerabilities to target GOF mutp53 proteins in PDAC. In response to mutp53 depletion only mutp53R248W harboring PDAC cells show STAT3 de-phosphorylation and reduced migration, again suggesting an allele-specific GOF in this cancer entity, similar to CRC. Moreover, mutp53R248W also exhibits the strongest constitutive complex formation with phosphorylated STAT3. The selective mutp53R248W GOF signals through enhancing the STAT3 axis, which was confirmed since targeting STAT3 by knockdown or pharmacological inhibition phenocopied mutp53 depletion and reduced cell viability and migration preferentially in mutp53R248W-containing PDAC cells. Our results confirm that mutp53 GOF activities are allele specific and can span across tumor entities.